Structural and spectroscopic characterization of tris (o-phenanthroline)iron(II) disaccharinate monosaccharin hexahydrate - Williams, Patricia Ana María (2000)
The crystal and molecular structure of the title compound, for short [Fe(o-phen)3](sac)2·(Hsac)·6H2O, has been determined by X-ray diffraction methods. It crystallizes in the monoclinic space group P21/n with a = 16.3190(1), b = 19.2890(1), c = 17.4490(2) A, β = 92.586(1)°, V = 5486.95(8) A3 and, Z = 4. The investigated compound constitutes the first example of a species in which uncoordinated saccharin and saccharinate anions are present in the structure. The crystallographic results reveal the subtle differences between the structure of the neutral molecule and its anion. The complex was also characterized by means of infrared, electronic, and 57Fe-Mossbauer spectroscopy. Its magnetic susceptibility was determined at room temperature and its thermal behavior investigated by means of thermogravimetric and differential thermal analytical techniques.